Clinical features, serological findings, and survival rate comparison between early versus late-onset systemic lupus erythematosus from 2000 to 2010, two centers experience - Alrashdi, Mousa N.; Sami Meateq, Alrasheedi; Alkhdairi, Ahmad; Alsulmi, H. A.; Faisal, Al Anzi; Almutlaq, A.; Shaheen, Naila A.; Balkhoyor, Abdulrahman; Alamri, Abdulrahman S.; Alrashid, Abdulrahman; Almaimony, Hesham; Al Motywea, Saleh; et al. (International Journal of Health Sciences, 2020)
Objective: The study aimed to compare the differences in patients diagnosed with early versus late-onset systemic lupus erythematosus (SLE) in terms of clinical features, disease activity, laboratory findings, and the 5-year survival rate. Materials and Methods: All newly diagnosed SLE patients from 2000 to 2010 in two tertiary centers in Saudi Arabia were enrolled. Retrospectively, early-onset SLE (18–49 years at the age of diagnosis) was compared to late-onset SLE (≥50 years at the age of diagnosis) using chart review of their clinical features, serology, and organ damage and disease activity. Results: A 196 SLE patients were included, 156 were in the early-onset SLE group while 40 in the late-onset SLE group. Arthritis was a frequent symptom in both groups. Proteinuria and anemia were prevalent in the early-onset SLE group (46.4%, 82.1%). The majority of the early-onset SLE (78.2%) group were anti-dsDNA positive compared to 42.5% in the late-onset SLE group. Similarly, 78.4% of the early-onset SLE group had hypocomplementemia compared to 44.7% in the late-onset SLE group. Renal insufficiency and thromboembolic events were more prevalent in the early-onset SLE group (24.2%, 13.6%), while pulmonary hypertension and hepatitis more prevalent in the late-onset SLE group (15% and 20%, respectively). Estimated 5-year survival analysis was lower in the late-onset SLE group compared to the early-onset SLE group. Conclusion: Early-onset SLE had a higher frequency of American College of Rheumatology criteria than the late-onset SLE group. However, the late-onset SLE group exhibited a higher frequency of medical comorbidities with a lower 5-year survival rate.